Guerra de Independencia e inicios de Revolución - Roura i Aulinas, Lluís (Cuadernos de Historia Moderna, 2009)
. This article analyzes the sense of the concepts "independence" and "revolution" applied respectively to the war against the Napoleonic troops and to the political situation lived in Spain between 1808 and 1814; paying special attention to the meaning that both concepts had at that time. This essay also studies the continuities and ruptures that characterized the long process of the Spanish liberal revolution, initiated in that moment, putting in evidence the shallowness of the nationalist myth surrounding this episode.
Keywords: Napoleonic era; Spain; Peninsular War (war of Independence); Liberal revolution; French Revolution; Enlightenment